2009
DOI: 10.2353/ajpath.2009.090007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Tumor Suppressor Protein α-Catenin by Ischemic Microenvironment

Abstract: Dysregulation or mislocalization of cell adhesion molecules and their regulators, such as E-cadherin, beta-catenin, and alpha-catenin, usually correlates with loss of polarity, dedifferentiation, invasive tumor growth, and metastasis. A subpopulation of alpha-catenin-negative cells within the DLD-1 colorectal carcinoma cell line causes it to display a heterogeneous morphological makeup, thus providing an excellent model system in which to investigate the role of alpha-catenin in tumorigenesis. We re-establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Our corroborative data further revealed the absence of α-catenin in DLD-1 single cells in contrast to DLD-1 cell clusters ( Fig. 2B ) ( 26 , 29 ). Accordingly, the subpopulations were termed as DLD-1 α-cat (epithelioid or forming cell clusters in col-I) and DLD-1 Δα-cat (round or forming single cell groups in col-I).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Our corroborative data further revealed the absence of α-catenin in DLD-1 single cells in contrast to DLD-1 cell clusters ( Fig. 2B ) ( 26 , 29 ). Accordingly, the subpopulations were termed as DLD-1 α-cat (epithelioid or forming cell clusters in col-I) and DLD-1 Δα-cat (round or forming single cell groups in col-I).…”
Section: Resultssupporting
confidence: 79%
“…In line with other studies ( 26 , 28 , 29 ), we isolated, propagated and characterized the two distinct DLD-1 subpopulations. The DLD-1 subpopulations grew either as compact cell clusters or as groups of single cells in 3D col-I ( Fig.…”
Section: Resultssupporting
confidence: 61%
“…Despite its critical role in cancer progression, the mechanism behind α-catenin downregulation is unclear. Some reports have suggested that DNA methylation, genetic alterations, and hypoxia in the cancer microenvironment play a role 4,23,27,28. Here, we provided novel insights into the regulation of α-catenin in CRC by focusing on the innate immune component NF-κB signaling.…”
Section: Discussionmentioning
confidence: 88%
“…Absent or reduced ␣-catenin expression increases tumorigenic characteristics in vitro (37) and has been documented in esophageal, lung, stomach, pancreatic, and colorectal cancers (36,38,50). It has also been associated with metastasis (10,11).…”
Section: Discussionmentioning
confidence: 99%